RETRACTED : Terhadap penguasaan konsep fisika siswa kelas X SMA Negeri I Lawang pokok bahasan suhu dan kalor - Desi Darma Wulan; Sutarman Sutarman; Bambang Tahan Sungkowo (Universitas Negeri Malang, 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) on this article.This paper has been found to be in violation of the Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in other academic publishing platforms.The document and its content has been removed from Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) and reasnable effort should be made to remove all references to this article.